STRATEGI INOVASI KEMASAN DAN PERLUASAN PEMASARAN ABON JANTUNG PISANG CISAAT MAKANAN KHAS SUBANG JAWA BARAT - Opan Arifudin; Udin Wahrudin; Fenny Damayanti Rusmana; Rahman Tanjung (Universitas Muhammadiyah Tapanuli Selatan, 2020)
To increase sales of a product, it takes a variety of innovations and marketing expansion. MSMEs with traditional food products must follow market trends to be able to continue to exist. Micro, Small, and Medium Enterprises (MSMEs) are the most strategic national economic sector and involve the lives of many people so that it becomes the backbone of the National economy. But the problem faced by businesses or small industries today is industrial management and marketing. With community service related to assisting MSMEs in traditional food, Abon jantung pisang expected to provide solutions in improving MSME welfare. The problem-solving method uses based on a management approach in increasing production and sales results with 4 (four) stages of program implementation, namely preparation, implementation, monitoring and evaluation, and reporting. The community service program carries out with packaging innovation following the rules of the Subang City Health Office and the need to attract consumer interest, as well as the expansion of marketing on online platforms and modern markets.